Dengue Hemorrhagic Fever and Its Correlation with The Weather Factor In Bandar Lampung City: Study From 2009-2018 - Yushananta, Prayudhy (Universitas Aisyah Pringsewu, 2021)
Dengue Hemorrhagic Fever (DHF) is the most serious vector-borne disease in Bandar Lampung. Dengue virus and its vector Aedes Aegypti are sensitive to weather changes, especially rainfall, temperature and humidity. This research objective was to determine the correlation between weather factors and dengue cases using the period 2009-2018. Data obtained from reports on the number of monthly cases of the in Health Office of Bandar Lampung City and daily climate reports from the Meteorology, Climatology and Geophysics Agency, which are converted into monthly averages. We found that the highest DHF cases were in January, February and March. Rainfall has a positive correlation with the number of dengue cases in 2011 (p-value = 0.012) and 2015 (p-value = 0.020). Each year, the rainy period precedes the start of the increase in dengue cases. Temperature has a negative correlation in 2014 (p-value = 0.036). Humidity has a positive correlation in 2014 (p-value = 0.024) and 2015 (p-value = 0.018). Rainfall has the greatest influence in relation to DHF cases in Bandar Lampung City (36.9%). These findings provide empirical evidence regarding the correlation between weather factors and DHF transmission and are expected to provide a scientific basis for the prevention and control of DHF. Abstrak: DBD adalah penyakit tular vektor yang paling serius di Kota Bandar Lampung. Virus dengue dan vektornya Aedes aegypti sensitif terhadap perubahan cuaca, khususnya curah hujan, temperatur dan kelembaban. Penelitian bertujuan mengetahui hubungan faktor cuaca dengan kasus DBD menggunakan periode tahun 2009-2018. Data diperoleh dari laporan jumlah kasus bulanan Dinas Kesehatan Kota Bandar Lampung, dan iklim harian dari Badan Meteorologi Klimatologi dan Geofisika yang dikonversi menjadi rata-rata bulanan. Kami menemukan, kasus DBD tertinggi pada bulan Januari, Februari, dan Maret. Curah hujan berkorelasi positif dengan jumlah kasus DBD pada tahun 2011 (p-value=0,012), dan 2015 (p-value=0,020). Setiap tahunnya, periode hujan mendahului dimulainya waktu peningkatan kasus DBD. Temperatur berkorelasi negatif pada tahun 2014 (p-value=0,036). Kelembaban berkorelasi positif pada tahun 2014 (p-value=0,024), dan 2015 (p-value=0,018). Curah hujan memberikan pengaruh terbesar dalam hubungan dengan kasus DBD di Kota Bandar Lampung (36,9%). Temuan ini memberikan bukti empirik mengenai hubungan faktor cuaca dengan penularan DBD, dan diharapkan dapat memberikan landasan ilmiah untuk pencegahan dan penanggulangan DBD.